Look Again - Montgomery, Charlotte; Illustrated by Drew-Brook, Deborah and Cormack, Allan (New York Scholastic, 1998)
Three children explore outdoors with a magnifying glass, binoculars, and a telescope.
Include Color illustrations
Keywords: Nature -- Nature study